2017
DOI: 10.15740/has/au/12.techsear(4)2017/932-937
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fungicides on seed mycoflora of sunflower at different storage periods

Abstract: SUMMARY :The efficacy of seven fungicides viz., captan, mancozeb, carboxin + thiram, carbendazim, tebuconazole, carbendazim + iprodione and metalaxyl against seed mycoflora of sunflower at recommended dosages and at different storage periods (1 day to 3 months) were studied. A total of 16 seed borne fungi belonging to 13 genera viz., Alternaria sp., Macrophomina phaseolina, Aspergillus flavus, Aspergillus niger, Aspergillus ochraceus, Aspergillus ustus, Emericella nidulans, Fusarium sp., Epicoccum sp., Cladosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This finding aligns with previous reports by Arulnandhy and Senanayak [6], who similarly observed that fungal infection was correlated with increased moisture content in infested soybean seeds. Srinivas et al [7] also noted that as the storage period increased, there was an observed rise in the percentage of seed infection caused by various seed mycoflora.…”
Section: Resultsmentioning
confidence: 95%
“…This finding aligns with previous reports by Arulnandhy and Senanayak [6], who similarly observed that fungal infection was correlated with increased moisture content in infested soybean seeds. Srinivas et al [7] also noted that as the storage period increased, there was an observed rise in the percentage of seed infection caused by various seed mycoflora.…”
Section: Resultsmentioning
confidence: 95%
“…The seed dressing fungicides viz., tebuconazole 25 % WG @ 0.2 %, carbendazim 12% + mancozeb 63% 75WP @ 0.25%, carbendazim 50% WP @ 0.1 %, carboxin 37.5% + thiram 37.5% 75WP @ 0.25%, thiophanate methyl 70% WP @ 0.1%, captan 75% WP @ 0.3%, mancozeb 75% WP @ 0.25%, etc. at their recommend dosages as well as at various concentrations were reported earlier as most effective against many seed and / or soilborne pathogenic fungi, by several workers [14,15,16,17,18,19,20,21,22,23]…”
Section: A Alternata Inhibitionmentioning
confidence: 98%